Edited Clean Version : Technology and the Culture of Control - Guins, Raiford (Book collections on Project MUSE., 2009)
Not long ago it would have been an absurd idea to purchase a television, CD or MP3 or DVD player, computer software, or game console with the intention of limiting its capabilities. However, as Raiford Guins demonstrates in Edited Clean Version, today's media technology is marketed and sold for what it does not contain and what it will not deliver. TVs equipped with V-chips, Internet filters, editing DVD players, clean-version CDs and MP3s, and game consoles with parental control features can block out, monitor, disable, and filter information. As Guins argues in this provocative book, consumer.